Math, asked by 9466916922sandeep, 3 months ago

please solve this problem​

Attachments:

Answers

Answered by kodammahesh999
0

Answer:

Step-by-step explanation:

i)3a+3

ii)3x+7

iii)4p-3

iv)2r-13

v)-2x-6y

vi)-3a-y

Answered by susantakumar17
0

Answer:

a) 3a+b-3

b) 3x+7

c) 4p-3

d) 2r-13

e) -2x-6y

f) -3a-y

Step-by-step explanation:

A) (4a+b)-(a+3)

= 4a+b-a-3

= 3a+b-3

B) (5x+3)-(2x-4)

= 5x+3-2x+4

= 3x+7

C) (7p-5)-(3p-2)

= 7p-5-3p+2

= 4p-3

D) (8r-4)-(6r+9)

= 8r-4-6r-9

= 2t-13

E) (3x-4y)-(5x+2y)

= 3x-4y-5x-2y

= -2x-6y

F) (4a-6y)-(7a-5y)

= 4a-6y-7a+5y

= -3a-y

Similar questions